2020
DOI: 10.1080/16549716.2020.1740419
|View full text |Cite
|
Sign up to set email alerts
|

Are people most in need utilising health facilities in post-conflict settings? A cross-sectional study from South Kivu, eastern DR Congo

Abstract: Background: The disruptive effect of protracted socio-political instability and conflict on the health systems is likely to exacerbate inequities in health service utilisation in conflictrecovering contexts. Objective: To examine whether the level of healthcare need is associated with health facility utilisation in post-conflict settings. Methods: We conducted a cross-sectional study among adults with diabetes, hypertension, mothers of infants with acute malnutrition, informal caregivers (of participants with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…Aiming to contribute to the strengthening of the DRC's health system through the integrated leadership of the HZ (28, 29), this study describes the state of leadership as experienced by operational-level health managers in rural areas in a context of crisis. The rural health zones in crisis in the DRC are similar in their organization and in the challenges they face (17,20,27,29,41), we believe that the results from these eight study areas will largely re ect the situation of all other areas in the same context. These results could represent one of the worst cases of the state of the DRC health system, with the crisis context playing as an aggravating factor (17,41) on the rural context, which is even worse than the urban context (42)(43)(44).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Aiming to contribute to the strengthening of the DRC's health system through the integrated leadership of the HZ (28, 29), this study describes the state of leadership as experienced by operational-level health managers in rural areas in a context of crisis. The rural health zones in crisis in the DRC are similar in their organization and in the challenges they face (17,20,27,29,41), we believe that the results from these eight study areas will largely re ect the situation of all other areas in the same context. These results could represent one of the worst cases of the state of the DRC health system, with the crisis context playing as an aggravating factor (17,41) on the rural context, which is even worse than the urban context (42)(43)(44).…”
Section: Discussionmentioning
confidence: 86%
“…As a result, along with the combined burden of infectious diseases and malnutrition, additional health problems directly related to crisis and armed con ict emerge, with major consequences for the overall health of the local population (18,19). The province of South Kivu in Eastern DRC is one of the most affected provinces by these recurring con icts (17,20). Hence the need to promote the leadership necessary to achieve greater resilience of the health system (16).…”
mentioning
confidence: 99%
“…Figure 2 shows a gradual increase in sources published, from 1 in 2006 to 12 in 2020 with dips in 2016 and 2018. Data for most sources were collected during conflict, except for 6 in Burundi, DRC, Kosovo, Myanmar, Nigeria, Sri Lanka, and Uganda that reported data collected after conflict [ 10 , 18 , 35 , 41 , 59 , 61 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…As the choice of place of delivery is often linked to women’s degree of autonomy [ 64 , 65 ], literature reports how interventions aimed at empowering women, particularly at the social and educational levels, have had a direct positive impact on MNH [ 66 , 67 ]. In the context of LICs, empowerment of women is crucial, yet decisions on healthcare might encompass factors beyond cost, including accessibility and perceived quality, influencing their preference for some facilities, regardless of the objectivized quality of services, as authors have observed in similar areas [ 68 ]. The government should prioritize providing financial protection or accessible, pro-poor healthcare systems in these areas where the state has little presence [ 69 , 70 ] while continuing to try to implement legislative mechanisms to discourage the unlicensed sector [ 71 ].…”
Section: Discussionmentioning
confidence: 99%